2023
DOI: 10.1007/s12672-023-00624-3
|View full text |Cite
|
Sign up to set email alerts
|

CT-measured body composition radiomics predict lymph node metastasis in localized pancreatic ductal adenocarcinoma

Abstract: Background To explored the value of CT-measured body composition radiomics in preoperative evaluation of lymph node metastasis (LNM) in localized pancreatic ductal adenocarcinoma (LPDAC). Methods We retrospectively collected patients with LPDAC who underwent surgical resection from January 2016 to June 2022. According to whether there was LNM after operation, the patients were divided into LNM group and non-LNM group in both male and female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Lymph node metastasis (LNM) is a common characteristic of advanced disease stages in iCCA and a strong predictor of poor prognosis in patients undergoing resection [12]. Studies have shown an association between BC and LNM in pancreatic ductal adenocarcinoma [13]. LNM occurs in approximately 39% of patients with iCCA who undergo lymph node dissection [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node metastasis (LNM) is a common characteristic of advanced disease stages in iCCA and a strong predictor of poor prognosis in patients undergoing resection [12]. Studies have shown an association between BC and LNM in pancreatic ductal adenocarcinoma [13]. LNM occurs in approximately 39% of patients with iCCA who undergo lymph node dissection [20].…”
Section: Discussionmentioning
confidence: 99%
“…To establish the relationship between these BC characteristics and clinical features, we conducted both univariate and multivariate logistic regression analyses. As complications were the focus of our analysis, we assessed overall complications according to the Clavien-Dindo Scale and infectious complications according to the Clavien-Dindo Scale, as well as liver failure, postoperative hemorrhage, and bile leakage according to the International Study Group of Liver Surgery (ISGLS) definitions [10][11][12][13].…”
Section: Associations Between Body Composition and Clinical And Labor...mentioning
confidence: 99%